Method for preparing copper-based powder pigment from waste circuit board glass fiber-based powder
By preheating, grinding and high-temperature heat treatment of the glass fiber-based powder of the waste circuit board, the copper-based powder pigment with elemental copper-silicon oxide-carbon composite is formed, which solves the problem of low utilization rate of the glass fiber-based powder material of the waste circuit board in the prior art, and achieves efficient reuse and color stability.
Patent Information
- Application Number
- CN202411940848.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The prior art is difficult to effectively improve the utilization rate and utilization value of glass fiber-based powder materials of waste circuit boards, and it is mainly concentrated on the addition of auxiliary materials with lower economic value, and the amount is small.
Through preheating treatment, grinding and sieving, the waste glass fiber-based powder and copper bromide are heat treated at high temperature under an inert atmosphere, and the pre-carbonized resin material is carbonized, and Cu2+ ions are reduced to copper elemental substances, and are combined into glass fibers to form a copper-silicon oxide-carbon composite copper-based powder pigment.
The prepared copper-based powder pigment has the properties of acid and alkali corrosion resistance, and remains stable in aqua regia, with low copper content but red color, and low raw material cost, achieving efficient reuse of glass fiber-based powder of waste circuit boards.
Smart Images

Figure CN119775804A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of inorganic pigments, and in particular relates to a method for preparing copper-based powder pigments by utilizing glass fiber-based powders of waste circuit boards. Background Art
[0002] With the rapid development of electronic and information technology, the speed of updating and iteration of electronic products is getting faster and faster. The output of electronic waste represented by waste circuit boards is increasing day by day, and there is a trend of accelerating growth worldwide. Therefore, the recycling and reuse of waste circuit boards has become a key area of environmental protection and urban health. At present, the recycling process of waste circuit boards in various countries in the world mainly focuses on the recycling and reuse of metal materials with high value content, such as copper, tin and silver. However, the recycling and reuse of base materials with relatively low apparent value and mainly composed of glass fiber and resin in waste circuit boards are less involved. The waste glass fiber-based powder material produced after the glass fiber is recycled by the metal recycling process will become a new and large amount of waste garbage. Therefore, the development of the recycling and reuse process of waste glass fiber-based powder materials has become an important direction of resource reuse research in the current electronic field.
[0003] At present, researchers have explored the recycling scheme of waste glass fiber-based powder produced after the metal recycling process of waste circuit boards. Zheng Jiaxing et al. reported that non-metallic powders such as glass fiber of waste printed circuit boards were added to nylon 6 materials to enhance the tensile strength of the materials. However, the study found that the addition of non-metallic powders such as glass fiber of waste circuit boards to nylon 6 materials would affect its impact resistance. The more the amount added, the faster the impact strength of the material decreased (Zheng Jiaxing et al., Performance Research of Nylon 6 Composite Materials Reinforced with Non-Metallic Powder of Waste Printed Circuit Boards [J]. Plastic Industry, 2013, 41 (2): 32.). The Chinese invention patent with publication number CN1654182A discloses a method for making recycled boards by hydraulic and hot forming of waste circuit board substrate particles containing glass fiber. The prepared boards can be used in small quantities in building materials such as floor tiles. The Chinese invention patent with publication number CN103073901A discloses a method for preparing asphalt modifiers by combining waste circuit board powder containing waste glass fiber with waste rubber. The amount of the prepared modifier added to asphalt is less than 20%. Therefore, the current utilization of waste glass fiber-based powder materials generated after the metal recycling process of waste circuit boards is mainly focused on the addition of auxiliary materials with lower economic value, and the amount used is relatively small. How to improve the utilization rate and utilization value of waste glass fiber-based powder materials after the metal recycling process is an urgent problem to be solved in the current recycling and treatment of waste circuit board waste materials. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing copper-based powder pigments using glass fiber-based powders of waste circuit boards. In this method, waste glass fiber-based powders generated after the metal recycling process of old circuit boards are subjected to a preheating treatment-grinding-screening method, so that the epoxy resin material is generated into a pre-carbonized resin material under preheating treatment, and most of the pre-carbonized resin material is screened out after grinding-screening to obtain glass fiber powders mainly containing glass fibers and a small amount of pre-carbonized resin material. In an inert atmosphere, the glass fiber powder is subjected to high-temperature heat treatment with copper bromide, so that the pre-carbonized resin material therein is carbonized to generate carbon material wrapped on the surface of the glass fiber, and Cu 2+ The ions are reduced to copper and compounded in the high-temperature softened glass fiber to form a copper-silicon oxide-carbon composite copper-based powder pigment.
[0005] The purpose of the present invention is achieved through the following technical solutions.
[0006] A method for preparing a copper-based powder pigment using glass fiber-based powder from waste circuit boards comprises the following steps:
[0007] Step 1) heating the waste glass fiber-based powder at 280° C. for 1 to 2 hours (preheating treatment), cooling to room temperature, grinding, sieving, and obtaining unsieved glass fiber powder on the sieve;
[0008] In the step 1), the operation of obtaining waste glass fiber-based powder includes: mechanically crushing the waste circuit boards, sieving with a 10-mesh screen, separating metals and waste by gravity (gravity method), and naturally drying the waste to obtain waste glass fiber-based powder.
[0009] In the above technical solution, the discarded circuit board is a discarded FR-4 type printed circuit board.
[0010] In the step 1), the sieve used for screening is 30 mesh.
[0011] Step 2) dissolving copper bromide in water, adding glass fiber powder, stirring at room temperature of 20-35°C for 4-6 hours, drying to obtain a mixture, heating at 550-650°C for 2-4 hours (heat treatment) under nitrogen protection, cooling to room temperature to obtain a coarse powder, soaking the coarse powder in dilute hydrochloric acid, filtering, and then soaking in sodium hydroxide solution, filtering, washing, and drying to obtain a copper-based powder pigment, wherein the ratio of copper bromide to glass fiber powder is (0.1-0.35): (0.5-1) by mass.
[0012] In the step 2), the ratio of glass fiber powder to water is (0.5-1):1 by mass.
[0013] In the step 2), the drying temperature is 80° C. and the drying time is 36 to 72 hours.
[0014] In the step 2), the temperature is raised to 550-650° C. at a rate of 5-8° C. / min.
[0015] In the step 2), the concentration of HCl in the dilute hydrochloric acid is 1 to 4 mol / L.
[0016] In the step 2), the sodium hydroxide solution is a mixture of sodium hydroxide and water, and the concentration of sodium hydroxide in the sodium hydroxide solution is 1 to 5 mol / L.
[0017] In the step 2), the soaking time is 4 to 8 hours.
[0018] In the step 2), the filtrate is washed with water until the pH value of the filtrate is neutral.
[0019] The copper-based powder pigment obtained by the above method.
[0020] The copper-based powder pigment is used in acid-resistant and / or alkali-resistant corrosion pigments.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The copper-based powder pigment prepared by the method of the present invention has the performance of acid and alkali corrosion resistance, and can also maintain its color in aqua regia, and has stability.
[0023] (2) The copper content of the copper-based powder pigment prepared by the method of the present invention is about 3% to 5%. The copper content is low and the amount of copper element used is small. The absorption of the visible red light in the range of 600 to 800 nanometers is weak, which is mainly manifested as surface reflection, making the copper-based powder pigment red in color.
[0024] (3) The raw materials used in the method of the present invention are low in cost, the preparation method is simple, and the waste glass fiber-based powder waste generated after the waste circuit board is recycled through the metal recovery process can be reused. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The surface morphology of the copper-based powder pigments prepared in Examples 1 to 3 and Comparative Example 1;
[0026] Figure 2 (a) SEM microscopic morphology and (b) energy spectrum data of the copper-based powder pigment prepared in Example 1;
[0027] Figure 3 (a) SEM microscopic morphology and (b) energy spectrum data of the copper-based powder pigment prepared in Example 2;
[0028] Figure 4This is the energy spectrum data diagram of the copper-based powder pigment prepared in Example 3;
[0029] Figure 5 This is the element distribution diagram of the copper-based powder pigment prepared in Example 3;
[0030] Figure 6 The X-ray diffraction pattern of the copper-based powder pigment prepared in Example 1 and the standard card of cubic copper element (PDF#04-0836);
[0031] Figure 7 The UV-visible absorption spectra of the copper-based powder pigment prepared in Examples 1 and 2;
[0032] Figure 8 The surface morphology of the copper-based powder pigments prepared in Examples 1 to 3 after being treated with aqua regia solution, wherein (a) is Example 1, (b) is Example 2, and (c) is Example 3;
[0033] Fig. 9 (a) is the surface morphology of red copper-based pigment. Fig. 9 (b) is the surface morphology of the red copper-based pigment treated with aqua regia solution. Fig. 9 (c) is the surface morphology of aqueous regia solution. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0035] In the following examples, the drugs and their manufacturers are as follows:
[0036] Copper bromide (purity: 99%) was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0037] Hydrochloric acid (purity: 35-38 wt%) was purchased from Tianjin Fengchuan Chemical Reagent Technology Co., Ltd.;
[0038] Sodium hydroxide (purity: 96 wt%) was purchased from Tianjin Hengxing Chemical Reagent Manufacturing Co., Ltd.
[0039] Nitric acid (purity: 65-68 wt%) was purchased from Tianjin Fengchuan Chemical Reagent Technology Co., Ltd.;
[0040] Silica powder was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0041] In the following embodiments, the operation of obtaining waste glass fiber-based powder includes: mechanically crushing the waste circuit boards, sieving with a 10-mesh screen, gravity sorting metals and waste (gravity method) through a wet shaking washing bed, recovering the metals, and naturally drying the waste to obtain waste glass fiber-based powder, wherein the waste circuit boards are FR-4 type waste printed circuit boards.
[0042] In the following embodiments, the waste glass fiber-based powder mainly includes: glass fiber and epoxy resin material.
[0043] In the following examples, the sodium hydroxide solution is a mixture of sodium hydroxide and water.
[0044] Examples 1 to 3
[0045] A method for preparing a copper-based powder pigment using glass fiber-based powder from waste circuit boards comprises the following steps:
[0046] Step 1) placing the waste glass fiber-based powder in a muffle furnace and heating it at 280° C. for H hours (preheating treatment), cooling it to room temperature, grinding it with an agate mortar, sieving it with a 30-mesh sieve, and obtaining unsieved glass fiber powder on the sieve;
[0047] Step 2) dissolving copper bromide in water, adding glass fiber powder, stirring at room temperature of 20-35°C for 4 hours, drying in an oven at 80°C for 36 hours to obtain a mixture, placing the mixture in an atmosphere protection furnace under nitrogen protection, heating to T°C at a rate of V°C / min, and heating at T°C for H T hours (heat treatment), cooled to room temperature to obtain a coarse powder, soaked the coarse powder in C1 mol / L dilute hydrochloric acid for H1 hour, filtered with a Buchner funnel placed with filter paper, collected the precipitate on the surface of the filter paper, and then soaked in C2 mol / L sodium hydroxide solution for H2 hours, filtered with a Buchner funnel placed with filter paper, collected the precipitate on the surface of the filter paper, washed with water until the pH value of the filtrate is neutral, and dried in an oven at 80°C for 36 hours after washing to obtain a red powdery copper-based powder pigment, wherein the ratio of copper bromide, glass fiber powder and water is W by mass.
[0048] W, H (unit: hour), V (unit: °C / min), T (unit: °C), H of the copper-based powder pigments prepared in Examples 1 to 3 T (unit: hour), C1 (unit: mol / L), H1 (unit: hour), C2 (unit: mol / L) and H2 (unit: hour) are shown in Table 1.
[0049] Table 1
[0050]
[0051]
[0052] Comparative Example 1
[0053] A method for producing a copper-based powder pigment comprises the following steps:
[0054] A commercially available red copper-based pigment (purchased from Tianjin Guangfu Fine Chemical Research Institute, the copper content in the red copper-based pigment is >99%) is mixed with silicon oxide powder with a particle size of 10 μm, and ground in an agate mortar for 20 minutes to obtain a copper-based powder pigment, wherein the ratio of the red copper-based pigment to the silicon oxide powder is 4:96 by mass, that is, the copper content in the copper-based powder pigment is 4wt%.
[0055] The copper-based powder pigments prepared in Examples 1 to 3 and Comparative Example 1 were recorded using a Sony digital camera. The results are as follows: Figure 1 As shown by Figure 1 It can be seen that although the copper content in the copper-based powder pigment prepared in Comparative Example 1 is close to that in the copper-based powder pigment prepared in Examples 1 to 3, the copper-based powder pigment prepared in Comparative Example 1 is white and slightly pale pink, while the copper-based powder pigments prepared in Examples 1 to 3 are granular powders and red in color.
[0056] The copper-based powder pigments prepared in Examples 1 to 3 were subjected to microscopic morphology and energy spectrum analysis using a Phenom Pro-X desktop scanning electron microscope. The results are as follows: Figures 2 to 5 As shown by Figures 2 to 5 It can be seen that the microstructures of the copper-based powder pigments prepared in Examples 1 to 3 are all cylindrical glass fiber structures.
[0057] The cylindrical glass fiber structure has a magnifying effect similar to that of a convex lens, which brings out the color of the copper element, so that the copper-based powder pigment with a very small copper content shows the color of the copper element.
[0058] The diameter of the copper-based powder pigment prepared in Example 1 is about 10-12 μm, the diameter of the copper-based powder pigment prepared in Example 2 is about 10-15 μm, and the diameter of the copper-based powder pigment prepared in Example 3 is about 8-12 μm. Figures 2 to 4 It can be seen that the main components of the copper-based powder pigments prepared in Examples 1 to 3 are copper, silicon, oxygen and carbon. The copper content in the copper-based powder pigment prepared in Example 1 is 3.62wt%, the copper content in the copper-based powder pigment prepared in Example 2 is 4.35wt%, and the copper content in the copper-based powder pigment prepared in Example 3 is 3.14wt%. Compared with the reported copper-based powder pigments, the copper-based powder pigment of the present invention uses less copper element and has a low copper content, but still presents a better red color. Figure 5 It can be seen that the copper element is less distributed than other elements. Figure 4 The results are consistent.
[0059] The copper-based powder pigment prepared in Example 1 was subjected to phase analysis using a Smart Lab intelligent X-ray diffractometer. The results are as follows: Figure 6 As shown by Figure 6It can be seen that the X-ray diffraction peak position of the copper-based powder pigment prepared in Example 1 corresponds to the standard diffraction peak position of the cubic copper single substance standard card (PDF#04-0836), indicating that the copper-based powder material prepared in Example 1 contains cubic copper single crystals, indicating that when preparing the copper-based powder pigment, in a high temperature environment, Cu 2+ The ions are reduced to copper and compounded in the high-temperature softened glass fiber, and a small amount of pre-carbonized resin material in the glass fiber powder will be carbonized at high temperature to generate carbon material, which is wrapped on the surface of the glass fiber. Therefore, the copper-based powder pigment of the present invention is a composite material of single copper-silicon oxide-carbon.
[0060] The copper-based powder pigment prepared in Examples 1 and 2 was tested for absorbance using a U-3900 UV-visible spectrophotometer. The results are as follows: Figure 7 As shown by Figure 7 It can be seen that the copper-based powder pigments prepared in Examples 1 to 2 have a strong light absorption capacity in the visible light region of 300 to 600 nm, but a weak light absorption capacity in the red light region of 600 to 800 nm, which mainly manifests as reflection, thus making the copper-based powder pigment red in color.
[0061] Example 4
[0062] Immersion experiment: A pigment with a mass of m0 was placed in an immersion solution and immersed for 2 hours. After immersion, it was rinsed with deionized water and dried in an oven at 90°C to constant weight. The weight was recorded as m1. The experiment was conducted twice in parallel to ensure the accuracy of the experimental results. The data obtained are shown in Table 2, wherein the pigment is one of the copper-based powder pigments prepared in Examples 1 to 3, and the immersion solution is dilute hydrochloric acid or sodium hydroxide solution. The concentration of HCl in the dilute hydrochloric acid is 1 mol / L, and the concentration of sodium hydroxide in the sodium hydroxide solution is 1 mol / L.
[0063] Table 2
[0064]
[0065] It can be seen from Table 2 that the copper-based powder pigments prepared in Examples 1 to 3 have almost no mass loss after being soaked in dilute hydrochloric acid or sodium hydroxide solution, and their mass retention rates are all above 99%.
[0066] Example 5
[0067] The copper-based powder pigments prepared in Examples 1 and 2 were placed in aqua regia solution for 1 hour to observe the color changes of the samples. The aqua regia solution is a mixture of nitric acid and hydrochloric acid. The ratio of nitric acid to hydrochloric acid is 1:3 by volume. The results are as follows: Figure 8 As shown in (a) and (b), Figure 8 As can be seen from (a) and (b), the copper-based powder pigments prepared in Examples 1 to 2 are still red in color.
[0068] The copper-based powder pigment prepared in Example 3 was placed in the above-mentioned aqueous regia solution and magnetically stirred for 1 hour, and the color change of the sample was observed. The results are as follows: Figure 8 As shown in (c), the copper-based powder pigment prepared in Example 3 is still red in color.
[0069] Comparative Example 2
[0070] The commercially available red copper-based pigment was placed in the above aqueous regia solution and allowed to stand for 0.5 hours, and the color change of the sample was observed. The results are as follows: Fig. 9 As shown in (b), Fig. 9 (b) shows that the red copper-based pigment is quickly dissolved in aqua regia solution. There is no red copper-based pigment in aqua regia solution, and the solution is light green. Fig. 9 As can be seen from (a), the commercially available red copper-based pigment is red. Fig. 9 As can be seen from (c), aqua regia solution is yellow.
[0071] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A method for preparing copper-based powder pigments using waste circuit board glass fiber-based powders, characterized in that: The following steps are involved: Step 1) heating the waste glass fiber-based powder at 280° C. for 1 to 2 hours, cooling to room temperature, grinding, sieving, and obtaining unsieved glass fiber powder on the sieve; Step 2) dissolving copper bromide in water, adding glass fiber powder, stirring at room temperature of 20-35° C. for 4-6 hours, drying to obtain a mixture, heating at 550-650° C. for 2-4 hours under nitrogen protection, cooling to room temperature to obtain a coarse powder, soaking the coarse powder in dilute hydrochloric acid, filtering, and then soaking in sodium hydroxide solution, filtering, washing, and drying to obtain a copper-based powder pigment, wherein the ratio of copper bromide to glass fiber powder is (0.1-0.35): (0.5-1) by mass.
2. The method according to claim 1, characterized in that The operation of obtaining waste glass fiber-based powder includes: mechanically crushing the waste circuit boards, sieving with a 10-mesh screen, separating metals and waste by gravity, and naturally drying the waste to obtain the waste glass fiber-based powder.
3. The method according to claim 2, characterized in that The waste circuit boards are FR-4 type waste printed circuit boards.
4. The method according to claim 1, characterized in that: The sieve is 30 mesh; the drying temperature is 80° C., and the drying time is 36 to 72 hours.
5. The method according to claim 1, characterized in that Calculated by mass, the ratio of glass fiber powder to water is (0.5-1):
1.
6. The method according to claim 1, characterized in that The temperature was raised to 550-650°C at a rate of 5-8°C / min.
7. The method according to claim 1, characterized in that The concentration of HCl in the dilute hydrochloric acid is 1 to 4 mol / L; The sodium hydroxide solution is a mixture of sodium hydroxide and water, and the concentration of sodium hydroxide in the sodium hydroxide solution is 1-5 mol / L.
8. The method according to claim 1, characterized in that The soaking time is 4 to 8 hours; washing with water until the pH value of the filtrate is neutral.
9. A copper-based powder pigment obtained according to the method according to any one of claims 1 to 8.
10. Use of the copper-based powder pigment according to claim 9 in acid-resistant and / or alkali-resistant corrosion pigments.
Citation Information
Patent Citations
Production method of asphalt modifier
CN103073901A
Preparation equipment for broken worn-out printed circuit board base plate material granules regeneration plate
CN1654182A
Method for separating and recycling each component material in waste printed circuit boards by using near-critical water
CN103949461A
Novel PCB / CCL waste regenerated resistance pulp and preparing method thereof
CN106847370A
Flat fiber modified light-colored polyamide composite for laser welding
CN107033588A